The rhetorical messages of Megawati Soekarnoputri’s speech in Aristotle’s framework - Anindita, Jaka; Muttaqin, Ridwan; Agustya, Sylvana Virgina; Supriadi, Dandi (Universitas Padjadjaran, 2024)
Background: The speech by Megawati Soekarnoputri, the 5th President of Indonesia, commemorating the 50th anniversary of Partai Demokrasi Perjuangan Indonesia (PDIP), has sparked significant public debate. While critics argue her speech was overly critical of President Joko Widodo, others view it as constructive criticism. Therefore, it is significant to examine Megawati’s actual perspective on the incumbent president and the real relationship between her position as chairperson and the president’s status as her cadre. Purpose: This study aims to analyze Megawati’s speech to uncover whether there is a misalignment between its intended message and impact which may have led to controversy. It analyzes the interpretation of people outside PDIP based on Aristotle’s rhetorical framework—ethos, logos, and pathos—to assess her communication strategy and public reception. Methods: A descriptive qualitative approach was used, with special interviews to gain a broader perspective. Triangulation was achieved by involving informants, along with observations, juxtaposing it with previous related research. Results: Based on the research findings, the author discovered that Megawati’s speech functioned primarily to communicate internally with the party’s members within her role as the chairperson. Based on rhetorical frameworks, the speech was exclusive to the internal context, and it could have been misinterpreted by people beyond the intended audience if the message had been amplified by mass and social media channels. Conclusion: The controversy arose because some receptors were not intended to receive her message due to massive distribution to the public either by mass media or social media. Implications: Interpretation of Megawati’s speech must be contextualized within the internal framework of PDIP reflecting its distinctive cultural and tradition attributes. The media outlets that cover this event should adopt a more balanced approach to present the realities to the public.